Transformasi Pendidikan: Pengaruh Media Pembelajaran Classpoint Terhadap Minat Belajar Materi IPS Siswa Madrasah Ibtidaiyah Palembang - Rizky, Muhammad; Jadidah, Ines Tasya; Putra Pratama, Muhammad Aldri; Nadilah, Azzahra Nurul; Apriana, Ayu (Universitas Islam Negeri Raden Fatah Palembang, 2023)
Interest in learning is an important aspect of the learning process. Some of the literature that the author found shows low interest in learning students at the elementary / MI level. The research method used is a quantitative type of quasi-experiment. The population in this study was a whole rush of grade VI students. The instrument trial sample comprised 114 respondents and class samples, namely IV.A and IV.B. The research showed an increase of 1.04 points in classes using class point learning media and independent sample t-test results showing a value of Sig.0.569. Based on these results, the author concludes that classpoint learning media has an effect but is not significant on students' learning interest in social studies material at MI Munawariyah Palembang.